What do Citizens Think of Cohesion Policy and Does it Matter for European identity?: A Comparative Focus Group Analysis - Pegan, Andreja; Mendez, Carlos; Triga, Vasiliki (My University, 2018)
This research paper investigates citizens’ perceptions and attitudes to EU Cohesion policy, its impact and the relationship with European identity. Discussions with 240 participants in 47 focus groups organised in 16 regions showed that the citizens of the EU have an implicit and cursory knowledge of Cohesion policy. Citizens recognise the importance of Cohesion policy for addressing regional disparities and improving the quality of life, but feel they are inadequately informed. Citizens want to have more say on how funds are allocated or governed in their area and expect the responsible authorities to improve their communication on Cohesion policy. Although many positive views were expressed about the impact of Cohesion policy on the region or city’s development, only a small number of participants considered that Cohesion policy has had a direct impact on their feeling of European identity. Furthermore, Cohesion policy can also have negative effects on European attitudes and identity if it is not perceived to be addressing local needs.